ANALISIS FEMINISME TERHADAP DINAMIKA KEKERASAN, MANIPULASI, DAN PERJUANGAN SUBJEKTIVITAS DALAM MEMOAR BROKEN STRINGS KARYA AURELIE MOEREMANS - Dita Hasibuan; Dora Perawati Sihotang; Yosi Aunike Sinuraya; Safinatul Hasanah Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study analyzes the memoir Broken Strings (2025) by Aurelie Moeremans through the lens of feminist literary criticism. The memoir documents the author's lived experience as a young woman subjected to emotional manipulation, sexual violence, and identity control by a significantly older man. Drawing on feminist theoretical frameworks—particularly the concept of the male gaze (Mulvey, 1975), gender-based violence (hooks, 2000), and women's subjectivity in autobiographical narratives (Smith & Watson, 2001)—this study identifies three central dimensions: (1) the construction of women as objects and property within unequal power relations, (2) the systematic silencing and erasure of women's agency through psychological manipulation, and (3) the process of self-reclamation and liberation as a form of feminist resistance. The findings suggest that this text functions not only as a document of personal trauma but also as a political act that challenges patriarchal norms normalizing the exploitation of young women. Broken Strings serves as a mirror reflecting how asymmetrical gender structures operate simultaneously within private and public spheres.